Предмет: Алгебра,
автор: kulaginavikycia11
Спростіть вираз (-1/3а^3b^2)^3 *(3a^5b)^2=
Ответы
Автор ответа:
0
Формулы:
(a^m)^n = a^(m * n)
a^m * a^n = a^(m + n)
(ab)^m = a^m * b^m
==================
( (-1/3)a³b² )³ * (3a⁵b)² =
= (-1/3)³(a³)³(b²)³ * 3²(a⁵)²b² =
= (-1/27)a⁹b⁶ * 9a¹⁰b² =
= (-1/3)a⁹⁺¹⁰b⁶⁺² = (-1/3)a¹⁹b⁸
Ответ: (-1/3)a¹⁹b⁸.
Похожие вопросы
Предмет: Физика,
автор: tsubereva08
Предмет: Литература,
автор: Evggeneiy
Предмет: Английский язык,
автор: ventixs1
Предмет: Биология,
автор: Аноним
Предмет: Биология,
автор: olgalanina115